Palaeoecological investigations and 230Th/U dating of Eemian interglacial peat sequence of Banzin (Mecklenburg-Western Pomerania, NE-Germany). (2nd November 2015) - Börner, Andreas; Hrynowiecka, Anna; Kuznetsov, Vladislav; Stachowicz-Rybka, Renata; Maksimov, Fedor; Grigoriev, Vasily; Niska, Monika; Moskal-del Hoyo, Magdalena
Abstract: A novel occurrence of an Eemian interglacial peat was identified in 2011 in a short-lived outcrop of the NEL-pipeline trench, near the village of Banzin, Germany. The profiles are situated in a shallow kettle hole within the undulated landscape of the Saalian glaciation. The distribution of dominantly till lithofacies in the Banzin area confirms the regional trend of Saalian tills with a locally higher abundance of Cretaceous clasts. In the Banzin kettle, at a depth of 2.2 m, lies a 0.5-m thick, strongly compressed Eemian peat layer. The buried Eemian peat layer is deformed by ice-wedge pseudo-morphological and mega crack structures, indicating a strong periglacial influence during Weichselian stadial phases. The post-Eemian sequence is subdivided into three units, beginning with a mixture of aeolian and gelifluction deposits, which are also modified by cryostructures. The top of the Banzin sequence is covered by a 0.5-m thick colluvisol layer of redeposited humic loam from the Late Weichselian/Holocene. The uppermost unit suggests that solifluction processes occurred in the last few hundred years, likely driven by intensive anthropogenic influence. Limnic sedimentation began during the Late Saalian period in a landscape characterized by herbaceous vegetation and heliophytes. During the latest interval of Saalian deglaciation, shallow waters of the basin most likely attained a depth below 3 m and were abundant in calcium carbonate. The beginning of Eemian interglacial peat accumulation (MIS 5e) is characterized by a dominance of light birch forests followed by pine. The ensuing optimum climate was dominated by the encroachment of oak forests and then hazel-oak forest, and sedimentation ceased in the basin during this phase. At the climatic optimum (PZ III/IV), the Eemian peat included remains of Ceratophyllum submersum and species of higher temperature requirements. The Banzin basin gradually became shallower and overgrown until the closing of its open water at the end of phase III/IVa. The lack of Cladocera species composition in the Eemian sequence proves isolated conditions of a shallow reservoir. We present the first results from NE-Germany for Eemian peat bog samples dated by the U–Th disequilibrium method ( 230 Th/U), using leachate alone (L/L) and total sample dissolution (TSD) analytical techniques. Isochron-corrected 230 Th/U ages of 118 ± 8/10 ka (L/L) and 121 ± 9/13 ka (TSD) were obtained. Both 230 Th/U dates ∼118–121 ka, obtained using two different techniques, confirm the biostratigraphical classification into the Eemian interglacial.